Clinical presentation of PTEN mutations in childhood in the absence of family history of Cowden syndrome. (March 2015) - Busa, T.; Milh, M.; Degardin, N.; Girard, N.; Sigaudy, S.; Longy, M.; Olshchwang, S.; Sobol, H.; Chabrol, B.; Philip, N.
Abstract: Background: PTEN gene (MIM 601628) is a tumor suppressor gene implicated in PTEN hamartoma tumor syndromes (PHTS) including Cowden syndrome, Bannayan–Riley–Ruvalcaba syndrome, and Proteus-like syndrome. Bannayan–Riley–Ruvalcaba syndrome is considered as the pediatric form of PHTS. More recently, children presenting autism spectrum disorders with macrocephaly (ASD-M) have been reported. Methods: We report clinical data from seven patients diagnosed in childhood with a PTEN germline mutation, excluding cases of familial Cowden syndrome. Results: This study underlines the variability of phenotype associated with PTEN mutations diagnosed at pediatric age. Most of the patients did not fulfill usual criteria of Bannayan–Riley–Ruvalcaba syndrome or ASD-M. Conclusion: PTEN testing should be considered in any child presenting with severe macrocephaly (>+4SD) and another feature of PHTS.